Officers of 42nd geological section, South African Engineer Corps: Geologists and geophysicists who created a unique unit that supported the British Army during the Second World War - Rose, Edward P. F. (Scientia Militaria - South African Journal of Military Studies, 2018)
Within British and Commonwealth forces of the Second World War, 42nd Geological Section was the only unit in which geologists and geophysicists deployed as a team into campaign areas. Water supply was a problem in many arid or semi-arid regions, and the section used geophysical methods (primarily surveys by electrical resistivity) to locate optimum sites for drilling boreholes to abstract potable groundwater – methods utilised also by the German Army but not otherwise by the British. Mobilised in August 1940, the section was operational first in East Africa and subsequently North Africa, the Middle East and the Mediterranean region until the end of the war. By September 1943, its core strength comprised five officers and 33 other ranks, commonly and widely deployed as detachments of one officer plus about seven other ranks. In total, thirteen officers are known to have served with the section, the first three from the Geological Survey of South Africa. Most were exceptionally well qualified and many achieved distinction in their civilian careers after the war. The section provides a little-known example of the significant specialist skills contributed by the South African Engineer Corps to the Allied war effort.